Impact of Maternal and Infant Antiretroviral Drug Regimens on Drug Resistance in HIV-Infected Breastfeeding Infants - Fogel, Jessica M. (2013)
BACKGROUND: The HPTN 046 trial evaluated the efficacy of extended infant nevirapine (NVP) administration for prevention of HIV transmission through breastfeeding. Infants received daily NVP to 6 weeks of age. HIV-uninfected infants (the intent-to-treat group) received daily NVP or placebo up to 6 months of age. We analyzed emergence of NVP resistance in infants who acquired HIV-infection despite prophylaxis. METHODS: HIV genotyping was performed using the ViroSeq HIV Genotyping System. Medians and proportions were used to summarize data. Two-sided Fisher’s exact tests were used to evaluate associations between categorical variables. RESULTS: NVP resistance was detected in 12 (92.3%) of 13 infants who were HIV-infected by 6 weeks and in seven (28%) of 25 infants who were HIV-uninfected at 6 weeks and HIV-infected at 6 months of age (6/8=75% in the NVP arm, 1/17=5.9% in the placebo arm, P=0.001). Among those 25 infants, 4 had mothers who initiated an antiretroviral (ARV) treatment regimen by 6 months postpartum. In all 4 cases, the treatment regimen included a non-nucleoside reverse transcriptase inhibitor (NVP or efavirenz). NVP resistance was detected in all four of those infants by 6 months of age (4/4=100%). In contrast, only three (14.2%) of the remaining 21 HIV-infected infants whose mothers did not initiate ARV treatment developed NVP resistance (P=0.003). CONCLUSIONS: Extended NVP prophylaxis significantly increased the risk of NVP resistance in infants who acquired HIV infection after 6 weeks of age. Treatment of maternal HIV infection was also associated with emergence of NVP resistance in HIV-infected, breastfed infants.